Intraoperative neuromonitoring of pelvic autonomic nerves during surgigal treatment of colorectal cancer: a review of the literature and the initial experience of our clinic - P. V. Tsarkov; V. S. Kochetkov; S. K. Efetov; Yu. E. Kitsenko; V. I. Stamov (Сибирский онкологический журнал)
Introduction. Urogenital and anorectal functional disturbances associated with the pelvic autonomic nerve damage are common complications of rectal cancer surgery. the search for methods of intraoperative identification of the autonomic nerve plexus is currently one of the key tasks in modern surgery of rectal cancer. the purpose of our study is to evaluate the role of intraoperative neuromonitoring in rectal cancer surgery.Material and methods. In 2017 we performed intraoperative neuromonitoring during rectal cancer surgery in two cases. the superior hypogastric plexus and the inferior hypogastric plexus were identified and the pelvic autonomic nerve was preserved in both patients. urogenital and anorectal functional outcomes were assessed in the postoperative period.Results. Satisfactory functional outcomes in the late postoperative period and at the 12-month follow-up suggest that intraoperative neuromonitoring may be useful in identification and prevention of the pelvic autonomic nerve damage in patients with rectal cancer.Conclusion. This method would be difficult to use routinely for intraoperative identification of the autonomic nerve plexus but could be especially useful for the study of pelvic physiology. With further development, the method of intraoperative neuromonitoring could help discover a technique that will improve the surgical treatment of rectal cancer. Further research using intraoperative neuromonitoring is needed to more precisely determine its value in the preservation of urinary, anorectal and sexual function.